(untitled) (ModaPalavra e-periódico, 2018)
The art of storytelling is intrinsic to human communication from its earliest form. Narratives date from the beginning of human evolution and, through them, meaningis givento everything that exists. Therefore, much has been said about the technique of storytelling in the corporate world, adding value to brandsadvertising and communication by telling stories to the consumer. Thus, this article aims to analyze the use of storytelling in the construction of brand identity, presenting a case study of the Portuguese shoes brand Josefinas. The company has a valuable position in the luxury market and develops the "sabrinas", inspired by ballet shoes, as well as moccasins, sandals, slippers and accessories. For this, the research used a qualitative and exploratory approach, verifying that the Josefinas identity was developed with storytelling as a starting point, strongly using this strategy in all online channels. We also observed that the brand reveals the purchase of their products as a search for identification, offering shoes as facilitators for the public to achieve personal and collective goals, such as raising self-esteem, guaranteeing egalitarian rights and social welfare.